1999
DOI: 10.1016/s0735-1097(98)00522-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of baseline lipids on effectiveness of pravastatin in the CARE trial

Abstract: Within the LDL cholesterol levels in CARE (115 to 174 mg/dl), baseline values influenced both the risk of events in the placebo group as well as the clinical effectiveness of pravastatin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…The CARE trial (22) provided evidence of cardiovascular benefits despite cholesterol levels in the normal range before statin treatment. Furthermore, multiple experimental studies have demonstrated reductions in myocardial infarct size in the absence of cholesterol lowering (16,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CARE trial (22) provided evidence of cardiovascular benefits despite cholesterol levels in the normal range before statin treatment. Furthermore, multiple experimental studies have demonstrated reductions in myocardial infarct size in the absence of cholesterol lowering (16,26).…”
Section: Discussionmentioning
confidence: 99%
“…The cholesterol-lowering effects of statins and their ability to reduce morbidity and mortality in cardiovascular disease have been proven in multiple clinical trials (23a, 24). Although reductions in serum lipids and plaque stabilization may account for part of the clinical benefit of statins (18,19), additional clinical evidence suggests mechanisms independent of diminishing hypercholesterolemia (22). A growing body of evidence implicates improvements in endothelial function and endothelium-derived nitric oxide (NO) as potential mediators (6,17).…”
mentioning
confidence: 99%
“…In the Program On the Surgical Control of the Hyperlipidaemias (POSCH), 15 Scandinavian Simvastatin Survival Study (4S), 16 Cholesterol And Recurrent Events (CARE) 17 and West of Scotland Coronary Prevention Study studies (WOSCOPS), 18 total plasma cholesterol and triglycerides values were positively correlated with cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Furthermore, in the CARE and LIPID trials, the benefits of pravastatin were diminished in patients with baseline LDL-C values less than 130 mg/dL. 19,21) In contrast, LIPS showed that the benefit of fluvastatin is equal regardless of the baseline cholesterol values, indicating that fluvastatin has beneficial effects other than its lipid-lowering effect in cardiac events. Recent reports have demonstrated that in addition to their lipid-lowering effects, statins have many pleiotropic effects, such as inhibiting oxidative stress, improving endothelial function, decreasing vascular inflammation, and enhancing plaque stability.…”
Section: Discussionmentioning
confidence: 99%